Dynamics of Psychological Characteristics of Female Patients of a Cosmetological Clinic During Treatment - E. S. Bagnenko (Учёные записки Санкт-Петербургского государственного медицинского университета им. Акад. И.П. Павлова)
Introduction. The relevance of the research is determined by the insufficient study of the psychological characteristics of female patients in the cosmetological clinic and the dynamics in the process of non-surgical correction and, in general, the psychological aspects of cosmetological treatment.The objective was to study the dynamics of the psychological characteristics of female patients of a cosmetological clinic in the process of medical correction.Methods  and  materials.  Using  psychodiagnostic  methods  “Neuropsychic  Adaptation  Test”  (NPA),  Wellness  Index (WHO-V),  Visual  Analogue  Scale,  Big  Five,  Quality  of  Life  Satisfaction  Questionnaire  (QL),  193  female  patients  of  the cosmetological clinic (mean age 39.19±0.8 years) were examined in the period before treatment and 3 months after it. Data processed by SPSS v. 25.0 using Pearson’s χ2 and Wilcoxon’s Z tests.Results. The results showed statistically significant changes in the course of treatment of 11 out of 20 psychodiagnostic indicators reflecting the positive dynamics of the following psychological characteristics: the level of neuropsychiatric adaptation (р=0.014), the level of psychological well-being (р=0.000), perception of one’s appearance (р=0.000), individual characteristics of the personality “self-consciousness” (р=0.003) and “personal resources” (р=0.001), overall satisfaction with quality of life (р=0.000) and its individual components.Discussion. There are showed limitations and research prospects associated with the further expansion of the range of studied psychological characteristics, their relationship with the severity of a cosmetic defect and, in a broader context - with the determination of the role of psychosocial factors in the mechanisms of development and the effectiveness of correction of facial skin defects.